Peran Orang Tua Terhadap Pendidikan Anak Usia Dini Dalam Hadis Nabi - Luthfie Noor Fithriasari (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2023)
Abstract. Nowadays many children develop inconsistently with their fitrah, this is influenced by environmental conditions that bring negative influences. One of the negative influences caused by environmental conditions on children's fitness is the polluting of children's creeds with incorrect beliefs. The cultivation of aqidah should be instilled from an early age and also lack control of bothparents or families. The purpose of this study is to determine the role of parents in early childhood education in the study of the prophet's hadith about every child born in a fitrah state and to prove the validity of the hadith. This research is a qualitative research in compiling and analyzing data using analytical descriptive methods with an approach to hadith studies and educational science. Based on a series of hadith tracing and research activities that include takhrij, sanad and matan criticism and its final assessment, it can be ascertained that the historical hadith of Bukhari and Imam Muslim about the concept of early childhood education about every child born in a fitrah state is a shahih hadith. Having fulfilled the requirements of the shahihan of a hadith i.e. Sanadnya is continued, All the scholars in the sanad are just and dhabith, in the sanad is spared from Syudzudz (gaffe) and 'illat (defect). Children are born in a fitrah state. Fitrah here is defined as the potential for religion, as well as the potential for non-religion. Parents have a responsibility to their children to develop according to their nature, responsible for their children's education